Similarities and Differences in Vietnamese-Japanese Language and Culture: A Study on the Domain of Words Indicating Kinship Relations from Role Schema Theory - Tran, Ly Thi Phuong (Animo Repository, 2023)
When it comes to the perception and processing of social information, role schema serves as a key concept in cultural linguistics, which processes information about the perception of humans to make sense of the complex world and society, information about people, social groups, and events; therefore, the theory is valuable in deciphering culturally constructed concepts with the full range of human experience expressed through the linguistic picture of each ethnic community. Recognizing that the hierarchical cultural characteristics of the two ethnic communities of Vietnam and Japan are most clearly shown through the kinship words in the family and display the meaning of the role of each person in each family and society, we have named the paper “Similarities and Differences in Vietnamese- Japanese Language and Culture: A Study on the Domain of Words Indicating Kinship Relations from Role Schema Theory.” In this paper, based on the theoretical perspective of the role schema in cultural linguistics, a survey and a study are conducted in detail on the similarities and differences between the Vietnamese and Japanese kinship words with collected data from Từ Điển Tiếng Việt (Vietnamese Dictionary; Phe, 2021) and Japanese dictionary - Shinmeikai Kokugojiden (Yamada et al., 2021). Based on the semantic characteristics, structural system, and cultural characteristics of Vietnam and Japan, the qualitative method is deployed to definitely demonstrate the characteristics through specific hierarchies in the class from kinship. In addition, quantitative methods are applied to draw diagrams and tabulate the number of kinship words in Vietnamese and Japanese to clarify the ability to operate similar and different cultural characteristics in these two languages. Thereby, we apply the research results of the article as a source of materials that not only support teaching and translation of a second foreign language but also serve as a foundation for applying situations of intercultural communication between Vietnamese and Japanese.